2020
DOI: 10.1177/0959354319898250
|View full text |Cite
|
Sign up to set email alerts
|

Publish less, read more

Abstract: A publication deluge has impeded rather than advanced theory in experimental psychology. Many researchers rely more on null-hypothesis significance testing than literature studies to determine whether results are worthwhile. Four problematic publication practices are symptomatic for the theoretical deficit: (a) reinventing the wheel, (b) the Proteus phenomenon, (c) mechanical (non) replications, and (d) the survival of discredited hypotheses. Remedies include the development of AI tools recommending semantical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 80 publications
0
41
0
Order By: Relevance
“…As Cummins put it: "In psychology, we are overwhelmed with things to explain, and somewhat underwhelmed by things to explain them with" (Cummins, 2000). For this reason, many scholars have argued that psychology's attention to statistics and replicability has distracted from a problem that runs much deeper: a crisis of theory (Borsboom, 2013;Borsboom et al, 2020;Cummins, 2000;Guest & Martin, 2020;Haslbeck et al, 2019;Meehl, 1990b;Muthukrishna & Henrich, 2019;Phaf, 2020;Robinaugh, Haslbeck, et al, 2019;Smaldino, 2019;Szollosi et al, 2019;Vaidyanathan et al, 2015;Van Rooij & Baggio, 2020).…”
Section: Data Rich and Theory Poormentioning
confidence: 99%
“…As Cummins put it: "In psychology, we are overwhelmed with things to explain, and somewhat underwhelmed by things to explain them with" (Cummins, 2000). For this reason, many scholars have argued that psychology's attention to statistics and replicability has distracted from a problem that runs much deeper: a crisis of theory (Borsboom, 2013;Borsboom et al, 2020;Cummins, 2000;Guest & Martin, 2020;Haslbeck et al, 2019;Meehl, 1990b;Muthukrishna & Henrich, 2019;Phaf, 2020;Robinaugh, Haslbeck, et al, 2019;Smaldino, 2019;Szollosi et al, 2019;Vaidyanathan et al, 2015;Van Rooij & Baggio, 2020).…”
Section: Data Rich and Theory Poormentioning
confidence: 99%
“…Although ensuring replicability, transparency, and openness are key to a healthier science (Chambers, 2019;Cohen, 2017;Moshontz et al, 2018;Nosek et al, 2018;Phaf, 2020;Poldrack et al, 2017;Zwaan, Etz, Lucas, & Donnellan, 2017), improving scientific inferences and building a cumulative science will require more. Psychology will benefit from diversifying its methods or the means through which data are collected and analyzed (e.g., Vazire, 2018).…”
Section: Diverse Methodsmentioning
confidence: 99%
“…When we look within psychology journals, it appears as though experiments have taken on a life of their own: 9 out of 10 articles in the Journal of Cognitive Neuroscience used experiments, PROMISES AND PERILS OF EXPERIMENTATION 13 though the proportions were smaller for Psychological Science (6 out of 10) and the Journal of Personality and Social Psychology (5 out of 9). Even recent large-scale multi-site replication projects (e.g., Many Labs Projects) seem to be doubling down on experimentation, presumably assuming that after identifying which experimental effects can(not) be replicated (see Phaf, 2020), the field will eventually regain its lost scientific respectability and credibility (Aschwanden, 2018;Nelson, Simmons, & Simonsohn, 2018). Ensuring replicability is crucial (but see Lewandowsky & Oberauer, 2020;Smaldino & McElreath, 2016), but what we suggest instead is the need to look beyond replicating experimental effects and consider approaches other than experimentation.…”
Section: Diverse Methodsmentioning
confidence: 99%
“…A number of suggestions have been advanced to improve the quality of replications. Phaf (2020) suggested that experimental work should always be complemented by thorough theoretical analyses. In the case of unsuccessful replications, this would allow for the discovery of potentially crucial (and as yet unexamined) factors that may explain the result.…”
Section: Replication Level: Group Effectsmentioning
confidence: 99%